Relationships Between Nitrogen Transformation Rates and Gene Abundance in a Riparian Buffer Soil - Lin Wu; Deanna L. Osmond; Alexandria K. Graves; Michael R. Burchell; Owen W. Duckworth (Environmental Management, 2012)

Chronic aspiration shifts the immune response from adaptive immunity to innate immunity in a murine model of asthma - Kuei-Ying Su; Anitra D. Thomas; Jui-Chih Chang; Jason H. Leung; Sean M. Lee; Zoie E. Holzknecht; Mary Lou Everett; W. Michael Foster; Monica Kraft; William Parker; R. Duane Davis; Shu S. Lin (Inflammation Research, 2012)

Development of a fluorescent-intercalating-dye-based reverse transcription loop-mediated isothermal amplification assay for rapid detection of seasonal Japanese B encephalitis outbreaks in pigs - C. J. Tian; Z. X. Lin; X. M. He; Q. Luo; C. B. Luo; H. Q. Yu; R. Chen; X. W. Wu; D. Z. Zhu; Z. J. Ren; Y. Z. Bi; J. Ji (Archives of Virology, 2012)

Identification and expression analysis of major histocompatibility complex IIB gene in orange‐spotted grouper Epinephelus coioides - D. Q. Lu; S. B. Yi; M. Yao; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2012)
In this study, complementary DNA (cDNA) and DNA sequences of major histocompatibility complex (MHC) class IIB genes ( mhcIIB ) were cloned from orange‐spotted grouper Epinephelus coioides . The gene structure of E. coioides mhcIIB consists of five exons and four introns, and its deduced amino acid sequence length is 249 amino acids, including a signal peptide, a peptide‐binding region, an IGC1 domain, a transmembrane region and a cytoplasmic tail. A phylogenetic study showed that E. coioides mhcIIB shared 32·0–79·1% identity with those of other teleosts and mammals. Real‐time reverse transcriptase (RT)‐PCR was performed to detect the class IIB gene expression in eight different tissues. To characterize the relationship between E. coioides mhcIIB gene and pathogens, in vivo and in vitro studies were performed. Challenge of Cryptocaryon irritans revealed that class IIB genes were down‐regulated after 24 and 48 h of challenge, and their expression was later restored at 72 h. Stimulation of isolated E. coioides leukocytes with lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (PolyI:C) significantly increased peripheral blood and spleen mhcIIB expression, while head kidney mhcIIB expression remained constant.

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)